Characterization of the chicken vimentin gene: Single copy gene producing multiple mRNAs - Zehner, Zendra E. (1983)
Genomic clones and cDNA plasmids were isolated for the intermediate filament protein vimentin from chicken. The identity of the various clones was determined both by mRNA selection [Paterson, B. M. & Roberts, B. E. (1981) in Gene Amplification and Analysis, Structural Analysis or Nucleic Acids, eds. Chirikjian, J. G. & Papas, T. S. (Elsevier, North Holland), Vol. 2, pp. 418-435] and nucleotide sequence analysis. Restriction analysis, hybridization data, and heteroduplex studies confirmed that all of the genomic isolates contained overlapping fragments of an identical vimentin gene. No evidence for the existence of a second vimentin gene could be found by a Southern analysis either by using coding fragments from the purified vimentin gene or by using cDNA plasmids as probe. Likewise, copy-number experiments verified that the vimentin gene was present only once in the haploid chicken genome. However, in a RNA blot analysis, at least two equally abundant vimentin mRNA species of approximately 2,200 and 2,500 nucleotides in length were detected in all RNAs tested. Sequence analysis revealed that the vimentin gene contained two sets of tandem polyadenylylation sites, 249 and 532 nucleotides downstream from the stop codon for protein synthesis. It is proposed that the larger mRNA species arise because of complete transcription of the 3′-end of the vimentin gene (560 nucleotides of 3′ nontranslated sequence), whereas the smaller mRNA species terminate after the first set of polyadenylylation sites.